An Unusual Case of Pinna Squamous Cell Carcinoma Arising Shortly after Resection of Atypical Fibroxanthoma - Eugene Omakobia; Ahmad Orabi; Richard Knights (Case Reports in Otolaryngology)
Objective. To report a unique case of pinna squamous cell carcinoma (SCC) arising shortly after resection of atypical fibroxanthoma (AFX) at the same site. Case report. An 81-year-old gentleman presented with a nodular right pinna lesion. This was excised, and histology confirmed AFX. Ten weeks later, an ulcerative lesion appeared at the resection site. This was confirmed to be SCC. Comparative analysis revealed no morphological resemblance between the initial AFX and new SCC lesion, and there was no evidence of initial misdiagnosis. Conclusion. SCC is the most common cancer involving the pinna. Whilst prolonged sun exposure is an important risk factor for SCC, chronic inflammation and wounds are other potential sources. We postulate whether SCC could have arisen from the previous scar tissue in a manner similar to Marjolin’s ulcer. This would be a highly unusual finding in the pinna and to our knowledge unprecedented in the English literature.